2001
DOI: 10.2165/00002018-200124010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Drug???Induced Kidney Disorders

Abstract: Nephrotoxicity is an inherent adverse effect of certain anticancer drugs. Renal dysfunction can be categorised as prerenal uraemia, intrinsic damage or postrenal uraemia according to the underlying pathophysiological process. Renal hypoperfusion promulgates prerenal uraemia. Intrinsic renal damage results from prolonged hypoperfusion, exposure to exogenous or endogenous nephrotoxins, renotubular precipitation of xenobiotics or endogenous compounds, renovascular obstruction, glomerular disease, renal microvascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
140
1
7

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(150 citation statements)
references
References 114 publications
2
140
1
7
Order By: Relevance
“…Gemcitabineinduced alopecia is rarely worse than grade 2, and no cumulative hepatic or direct renal toxicities have been reported for gemcitabine [51]. However, the development of thrombotic microangiopathy may result after extended use of gemcitabine [41], and potentially life-threatening hemolytic uremia can occur secondary to this effect [52,53].…”
Section: Gemcitabinementioning
confidence: 99%
“…Gemcitabineinduced alopecia is rarely worse than grade 2, and no cumulative hepatic or direct renal toxicities have been reported for gemcitabine [51]. However, the development of thrombotic microangiopathy may result after extended use of gemcitabine [41], and potentially life-threatening hemolytic uremia can occur secondary to this effect [52,53].…”
Section: Gemcitabinementioning
confidence: 99%
“…10) Patients treated with cisplatin commonly show a glomerular filtration rate 20-40% lower than people without treatment. 11) Other clinical data have also shown that approximately one third of patients develop renal injury in the days following cisplatin treatment, with reduced glomerular filtration rates, increased blood urea nitrogen and serum creatinine, and imbalanced electrolytes. 12,13) In cisplatin nephrotoxicity, the key pathological features are renal tubular cell injury and death.…”
mentioning
confidence: 98%
“…11 Optimally, a through assessment of kidney function, including evaluating glomerular filtration, as well as proximal tubule and distal tubule function is recommended in people treated with cisplatin. 12 Glomerular filtration rate can be evaluated with inulin, creatinine, iohexol, and radioisotopes such as 99m Tc diethylenetriamine pentaacetic acid plasma clearance. 4 Proximal tubule function is assessed by measuring fractional excretion of glucose, uric acid, calcium, phosphorus, and magnesium as well as determining the renal threshold for phosphate, bicarbonate, and low molecular protein excretion.…”
Section: Discussionmentioning
confidence: 99%
“…4 Proximal tubule function is assessed by measuring fractional excretion of glucose, uric acid, calcium, phosphorus, and magnesium as well as determining the renal threshold for phosphate, bicarbonate, and low molecular protein excretion. 12 Urine osmolality and pH evaluate distal tubule function. 12 Measuring urine protein and enzyme excretion and evaluating urine sediment complete the urinalysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation